2016
DOI: 10.5755/j01.ms.22.2.12932
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Effect of Disorientation Angle on the Deformation of Carbon Composite Plates

Abstract: The disorientation angle, a technological error in the manufacture of carbon composite materials, is the most important determinant of deviation of the obtained surface shape from the planned shape. Elimination of these defects results in additional time and financial costs. Therefore, this study examined the influence of the disorientation angle experimentally using carbon plastic (KMU-4l) composite plates measuring 300 × 300 mm with different basic structures such as 0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…They found that tensile properties influenctial factor of the laminated composites were the fibre orientations. In other work, Bitkina et al , [40] performed on experimental of the effect of disorientation angle on the deformation of carbon composite plates. These results are applicable to industrial scenario because eight-layer carbon composite structures have various applications such as aviation, wind turbine, aerospace, etc.…”
Section: Carbon Fibre Reinforced Polymer (Cfrp)mentioning
confidence: 99%
“…They found that tensile properties influenctial factor of the laminated composites were the fibre orientations. In other work, Bitkina et al , [40] performed on experimental of the effect of disorientation angle on the deformation of carbon composite plates. These results are applicable to industrial scenario because eight-layer carbon composite structures have various applications such as aviation, wind turbine, aerospace, etc.…”
Section: Carbon Fibre Reinforced Polymer (Cfrp)mentioning
confidence: 99%